Ethnic vegetables for urban nutrition (Current Horticulture, 2024)
The use of wild plants as food is an integral part of the culture and tradition of many indigenous communities around the world. Asia can be considered as main gene center for vegetables. In India vegetables and spicy herbs are obligatory compounds of our daily diet which provide high amount of vitamins and bioactive substances. Nevertheless, indigenous vegetables are underestimated concerning their nutritional and economical value in their home states and underutilized so far. The global diversity of vegetable crops is estimated to be around 400 species, of which about 80 species of major and minor vegetables have originated in India. Many of these vegetables could be used as functional foods. Ethnic vegetables are vegetables which are traditionally grown in India. Nutrient dense indigenous vegetables have a potential role in improving human nutrition. Ethnic vegetables availability is more in rural areas because of this reason urban people prefer exotic vegetables which are less nutritious than ethnic vegetables. The cultivation of these vegetables on larger scale should be increased in urban and peri-urban areas. Home gardening and urban farming need to be enhanced for production of ethnic vegetables to improve the supply to the urban people.
Keywords: Ethnic vegetables; Urban nutrition; Spicy herbs; Bioactive substances; Global diversity